Avaliação do desempenho de argamassa de revestimento com resíduos de construção e demolição aplicando a metodologia de projeto robusto - Maculan, Laércio Stolfo (2009)
The construction industry is responsible for much of the waste generated in the planet. Recycling and/or reusing construction and demolition waste (CDW) are the most practical way to use the characteristics of such materials. Among the various applications of the CDW in the construction industry, the use in the manufacturing of rendering mortars stands out for its potential use. However, a CDW mortar must meet the same quality requirements of a conventional mortar. This study aimed to evaluate the effect of different compositions of rendering mortars with the addition of CDW. The experimental approach used in this study was based on the methodology of robust design. The controlled variables and their ranges were: the CDW Sand/Total Sand ratio (0.25 to 0.75); the Cement/Total Binder ratio (0.3 to 0.7); the percentage of ceramic in the CDW sand (25 to 75%), and the consistency (240 to 280 mm). The response variables were: the water retention and the incorporated air content (in fresh state); the compression strength, the flexural tensile strength, adhesion strength and length of cracking (in hardened state), at 28 days of curing. The results obtained for the response variable incorporated air content showed that the amount of cement, the consistency, the amount of CDW, and the amount of ceramic material in the CDW had an influence on this property. For higher cement contents there was an increase in the incorporated air content. However, for high levels of both CDW and amount of ceramic material, a reduction in this variable was observed. For the response variable water retention, the factor that had the most significant influence was the amount of lime. Also, it was observed an increase in water retention by increasing the amount of ceramic material and the amount of CDW. Concerning the compressive strength, the flexural tensile strength, and the adhesion strength, it was concluded that the amount of cement was the main influence on the results. Also, it was observed that the amount of both CDW and ceramic material had a significant influence on the adhesion strength. Regarding the length of cracking per square meter of mortar, there was a significant influence only of the amount of cement. At higher levels of this factor there was much less cracking when compared to the low levels of the same factor. The optimization analysis in conjunction with the robust design methodology allowed the determination of an optimal condition or zone, where, in principle, mortars are obtained with better overall performance, satisfying the required performance and improving the robustness of the product. The best mixture proportion was obtained for the following combination: CDW Sand/Total Sand ratio of 0.59; Cement/Total Binder ratio of 0.60; percentage of ceramic in the CDW of 62.5%, and consistency of 250mm